Metode Talfiq dan Takhayyur dalam Pengaruh Moderasi Bermazhab di Lingkungan Masjid Kapasa Raya Kecamatan Tamalanrea Kota Makassar - Sabir, Muh; A. Gazali, Muh. Rakasiwi (Media Hukum Indonesia (MHI), 2025)
This research aims to examine the practice of amaliah in worship through the method of talfiq and takhayyur in its influence in the moderation of sects in Kapasa Raya District of Makassar City. The study belongs to the classification of field research using phenomenological and normative jurisprudential approach, the research participants included congregants, imams and religious figures in the mosque environment The data was obtained through interviews, observations as well as documentation methods after which the collected data were processed and analyzed in data reduction and analysis in 3 stages. The results of the study indicate that both methods play a very important role in the dynamics of the influence of moderate sects in the environment of the Kapasa Raya Mosque. a mosque, but if a person is takhayyur or choose a sect or opinion that can guide his practice then it will organize and menata activities regarding religious worship of the congregation that affects the moderation of sects among the congregation of the mosque. The implication of this research is expected to the community and religious figures in the environment of the Kapasa Raya Mosque as the Qibla of Amaliyah guidelines that are very influential among the congregation of the mosque to improve the understanding of moderation kemazhaban by not mixing worship practices.